2018
DOI: 10.17219/acem/75618
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of peripheral nerve and autonomic nervous system function and the stage ofmicroangiopathy in patients with secondary Raynaud’s phenomenon in the course of connective tissue diseases

Abstract: Correct standard conduction velocity and CVD testing in patients with SPR suggest that vasomotor disturbances may occur in CTD regardless of peripheral neuropathy. The lack of relationship between SSR and microangiopathy could confirm that these 2 processes occur independently in patients with CTD-related SRP. Autonomic nervous system impairment together with normal peripheral nerve function suggest the central origin of CTD-related SRP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
1

Year Published

2018
2018
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 21 publications
0
6
1
Order By: Relevance
“…Increased latency in SSR may originate from milder neuropathic damage or from loss of thicker axons, changes in cholinergic fibres and/or sweat glands and synaptic transmission interruption through central processing. 23 Since there was no evidence of afferent somatic fibres or central nervous system or sweat gland diseases in the present study, it is suggested that the source of SSR latency abnormalities might be the sympathetic efferent nerves.…”
Section: Discussioncontrasting
confidence: 53%
See 2 more Smart Citations
“…Increased latency in SSR may originate from milder neuropathic damage or from loss of thicker axons, changes in cholinergic fibres and/or sweat glands and synaptic transmission interruption through central processing. 23 Since there was no evidence of afferent somatic fibres or central nervous system or sweat gland diseases in the present study, it is suggested that the source of SSR latency abnormalities might be the sympathetic efferent nerves.…”
Section: Discussioncontrasting
confidence: 53%
“…noted a significantly low SSR amplitude and long latency in their palms and soles. 23 In patients with SRP, no relationship was found between SSR and microangiopathy; this confirmed that these two processes occur independently in patients with SRP. The authors concluded that normal peripheral nerve function with impaired ANS suggested the central origin of SRP.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…19 Central autonomous involvement has also been suggested to be important in the pathogenesis of connective tissue disease-associated RP. 20 Cold stimuli causes relocation of alpha 2c-adrenergic receptors from the Golgi apparatus to the cell surface, through activation of the rho kinase, which then increases the sensitivity of contractile proteins and subsequent vasoconstriction. 21 Increased alpha 2c-adrenergic expression in vascular smooth muscle cells has been reported in RP.…”
Section: Vascularmentioning
confidence: 99%
“…Fries also demonstrated the increased skin resistance to the passage of weak electric current in the digits of patients with SSc [ 10 ]. This was interpreted as autonomic underactivity, and it was suggested that this might be a compensatory mechanism to increase blood flow to ischemic areas [ 18 ].…”
Section: Discussionmentioning
confidence: 99%